1990
DOI: 10.1002/path.1711620308
|View full text |Cite
|
Sign up to set email alerts
|

In situ distribution of transforming growth factor α in normal human tissues and in malignant tumours of the ovary

Abstract: The distribution of transforming growth factor alpha (TGF-alpha) in human normal tissues from the uterus, Fallopian tube, ovary, small and large intestine, lung, spleen, kidney, and skin was studied by immunohistochemistry. TGF-alpha was found in epidermis, bronchial epithelium, intestinal mucosa, renal tubules, endo- as well as in exocervical and endometrial epithelium, and in the serous epithelium of the Fallopian tube. No TGF-alpha was detected in the stromal components of any of the tissues nor in any of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…We can discuss our data qualitatively or quantitatively. Qualitatively, our detection of TGF-· in the sera of controls and ovarian cancer patients is consistent with the radioimmunoassay (RIA) results of Owens and Leake [16] who found TGF-· present in the tissue of approximately 84% of normal ovaries, and with the follow-up study of Owens et al [17] and with Kommoss et al [18] who performed immunohistochemistry on frozen tumor tissue. Only 6 of our 36 ascites samples had detectable TGF-· levels.…”
Section: Discussionsupporting
confidence: 76%
“…We can discuss our data qualitatively or quantitatively. Qualitatively, our detection of TGF-· in the sera of controls and ovarian cancer patients is consistent with the radioimmunoassay (RIA) results of Owens and Leake [16] who found TGF-· present in the tissue of approximately 84% of normal ovaries, and with the follow-up study of Owens et al [17] and with Kommoss et al [18] who performed immunohistochemistry on frozen tumor tissue. Only 6 of our 36 ascites samples had detectable TGF-· levels.…”
Section: Discussionsupporting
confidence: 76%
“…Although these authors observed EGF and TGF-a in both epithelial and extraepithelial (such as muscular layer) tissues, we failed to demonstrate the expression of these proteins in extraepithelial tissues. Our result was consistent with a previous report [21] that TGF-a was localized to epithelial cells in the human fallo pian tube.…”
Section: Discussionsupporting
confidence: 83%
“…there is a significant correlation between the presence of mRNA in neoplastic tissue and the expression of the respective peptide [56,57], While it has been reported that EGF mRNA is present in only 33% of gastric carci nomas. abundant TGF-a mRNA and EGF-R mRNA is found in all gastric carcinoma cell lines [36, 58.…”
Section: Expression Of Egf Tgf-a and Egf-r In Gastric Adenocarcinomasmentioning
confidence: 93%